The Trans-Pacific Strategic Economic Partnership Agreement: High Standard or Missed Opportunity? - GAO, Shuchao Henry (Institutional Knowledge at Singapore Management University, 2009)
When the Trans-Pacific Strategic Economic Partnership Agreement (P4 Agreement) was signed in 2005, it was hailed as a “high-standard” agreement that could serve as a model within the Asia-Pacific region and attract other countries in the region to join as members. This claim seems to have received support from recent events, such as the launch of the accession negotiation by the US and the expression of interests from Australia, Peru and Vietnam. This article provides a critical analysis on whether the P4 Agreement is a “high-standard” agreement as its members have claimed. In the view of the author, the P4 Agreement can only be regarded as a “high-standard” agreement if the trade liberalization opportunities and rules restricting trade protections provided for under the agreement are:1. better than the ones provided for under the WTO Agreements;2. better than the ones provided for under other agreements concluded between other WTO Members who are not members to the P4 Agreement;3. better than the ones provided for under the other agreements concluded between the members of the P4 Agreement with non-members to the P4 Agreement;4. better than the ones provided for under the pre-existing agreements concluded between the members of the P4 Agreement themselves before the P4 Agreement was concluded. After careful study, this article notes that the P4 Agreement does not compare favorably with other agreements, especially with regard to the following sectors: linearization of tariffs on trade in goods, non-tariff measures, rules on trade remedies, and opening up of the services market. This is rather disappointing, especially as all of the current members of the P4 Agreement are widely regarded as champions of free trade. In the next section, the author discusses the possible factors that might explain for the mismatch between the rhetoric and reality of the P4 Agreement. The article concludes by considering how these factors will play out in the negotiations with the countries which might be interested in acceding to the Agreement, possible implications for the future of the P4 Agreement itself and the wider prospect of trade liberalization in the Asia Pacific region in general, as well as how the P4 Agreement could be re-engineered to truly achieve its stated purposes.